The Techniques That Used by Lecturer In Teaching Speaking Subjects At The Second Semester Students Of The English Study Program Of The Muhammadiyah University Of Bengkulu - Fetriani (Edelweiss : Journal Of Innovation In Educational Research, 2024)
This study was aimed to investigate what technique used by lecturer in teaching speaking of the second semester students at Muhammadiyah University of Bengkulu. This research was qualitative research. The data were collected from the handy cam, observation checklist, and interview. The finding of the research indicated: the one lecturer applied six techniques, they were asking question, pair group discussion, situational practice, dialogue, role play, and picture discussion. Lecturer two only applied two techniques, they were speeches and debate. The most dominant technique was pair group discussion technique,